Dominant deafness–onychodystrophy syndrome caused by an ATP6V1B2 mutation. Issue 4 (8th February 2017) - Menendez, Ibis; Carranza, Claudia; Herrera, Mariana; Marroquin, Nely; Foster, Joseph; Cengiz, Filiz Basak; Bademci, Guney; Tekin, Mustafa
Key Clinical Message: Our report clarifies the role of ATP6V1B2 in patients with deafness and onycho‐osteodystrophy and confirms that a recurring ATP6V1B2 c.1516C>T [p.(Arg506*)], variant causes dominant deafness–onychodystrophy (DDOD) syndrome. Abstract : Our report clarifies the role of ATP6V1B2 in patients with deafness and onycho‐osteodystrophy and confirms that a recurring ATP6V1B2 c.1516C>T [p.(Arg506*)], variant causes dominant deafness–onychodystrophy (DDOD) syndrome.